2016
DOI: 10.3402/gha.v9.30215
|View full text |Cite
|
Sign up to set email alerts
|

Vietnamese mother's conceptions of childhood overweight: findings from a qualitative study

Abstract: BackgroundChildhood overweight and obesity is a new and emerging problem in Vietnam. The so far observed prevalence increases have pointed to the need for public health intervention strategies with parents as crucial resources for change.ObjectiveThe aim of this study was to understand mothers’ conceptions of childhood overweight.DesignFour focus group discussions were conducted with a total of 33 mothers of preschool children, 4–6 years old, living in urban and rural districts of Hanoi, Vietnam. The discussio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
3
9
0
Order By: Relevance
“…Most carers defined overweight subjectively from physical appearance. This finding is in keeping with studies from Germany, [ 30 ] the United Kingdom, [ 22 ] the United States, [ 23 , 31 ] and in Vietnam [ 32 ]. While some carers knew how to define overweight objectively, this knowledge is not very useful when they do not know their child’s current weight or height.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Most carers defined overweight subjectively from physical appearance. This finding is in keeping with studies from Germany, [ 30 ] the United Kingdom, [ 22 ] the United States, [ 23 , 31 ] and in Vietnam [ 32 ]. While some carers knew how to define overweight objectively, this knowledge is not very useful when they do not know their child’s current weight or height.…”
Section: Discussionsupporting
confidence: 90%
“…Some carers agreed with the ‘chubbier is healthier’ concept that is also found in other cultures. For example in Turkey (plump kids are healthy), [ 34 ] Vietnam (chubbiness is good), [ 32 ] the United States (“baby fat” is cute and healthy [ 31 ]; a bigger infant is a better infant [ 28 ]) and the United Kingdom (a big baby is a healthy baby) [ 35 ]. The concept of overweight symbolising family wellbeing is also found in China [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies show high rates of mixed feeding [51] and bottle-feeding [52] in Vietnamespecially supplemental feeding with sweetened liquids and foods [53] that is associated with increased risk of child obesity [54]. Children of mothers with higher education may have greater risk of ow/ob because educated mothers may be working outside the home, curtailing the duration of breastfeeding, and leaving the child's caregiver with money to buy "treats" such as snacks or sugary drinks [55,56]. Furthermore, the common practice of giving children sweets as a reward leads children to associate sugary foods and beverages with positive emotions, and reduces preference for non-sugary options such as vegetables, unsweetened milk, and water [57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we also found that children who drink powdered milk and milk products have higher odds of being ow/ob at age 8. In a recent qualitative study by Do et al, mothers acknowledged that one way to improve children's diets is to switch from milk with sugar to milk without sugar [55]. While milk and powdered milk have some nutritional benefits, the sugar and other additives may be a significant contributor to excess weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…Focus group interviews are becoming more used for data collection in studies using phenomenography as method for data analysis (Arveklev, Berg, Wigert, Morrison-Helme, & Lepp, 2018;Loan Minh et al, 2016). The choice of using focus groups in this study was based on the apprehension that if a researcher asks about evidence-based nursing, the participant (as a FLNM) could experience this as a questioning of the FLNM's intention to work with that particular question.…”
Section: Study Limitations and Strengthsmentioning
confidence: 99%